A revision of the clam shrimp Australimnadia Timms and Schwentner, 2012 (Crustacea: Spinicaudata: Limnadiidae) with two new species from Western Australia - Timms, Brian V.; Schwentner, Martin (Zootaxa, 2017)
The original type species of Australimnadia is made a junior synonym of A. grobbeni, originally described as Limnadia grobbeni Daday, 1925. A second species of Australimnadia is described from Onslow, Western Australia; it differs in having unique egg morphology and is distinct in many morphological characters, including those of the telson and cercopod, but also of the thoracopods. Its validity is confirmed by molecular differences between the two species in COI and EF1α. A third species from southwestern Western Australia is separated morphologically by unique spination of the telson and setation of the cercopod, and by its egg morphology.